The Impact of Digital Marketing Adoption on Sustainable Growth Mediated by Firm Performance: An Empirical Study of SMEs - Dianta, Indra Ava; Sinaga, Herty Ramayanti; Wicaksono, Jentoro; Zusrony, Edwin (Jurnal Informatika Ekonomi Bisnis, 2025)
MSMEs embrace the strategy of sustainable growth through firm performance by adopting digital marketing after the Covid-19 pandemic. The purpose of this study is to explain the direct effect of the adoption of digital marketing on the sustainable growth mediated by firm performance of MSMEs. The population in this study was all MSMEs operating in Salatiga City. The sample and limiting samples were 100 respondents who used a purposive sampling method. The data was collected using a questionnaire with a Likert scale. The data was analyzed using covSEM-PLS and the data was processed using the SmartPLS application Version 4.1.1.2. The conclusion of the study is that the variables of adoption of digital marketing have a direct influence on sustainable growth in MSMEs. Firm performance is able to mediate the effect of the variables of adoption of digital marketing on sustainable growth in MSMEs.